Pindar and the poetics of permanence - Spelman, Henry 1987- (Oxford classical monographs, 2018)
Taking Pindar as its focus, this volume is a book-length study devoted to the rhetoric and realities of literary permanence in early Greek poetry. It explores how Pindar's odes address their first and later audiences, and how the poet's vision of his literary world illuminates the context within which he anticipated its permanence